Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM) - Novianti, Ardya ; Epi, Yus (TIN: Terapan Informatika Nusantara, 2023)
SAK EMKM aims to make it easier for SMEs to gain access to funding from various financial institutions, so the presence of SAK EMKM is expected to help SMEs in Indonesia in preparing financial reports. The problem that often occurs is that SMEs are not yet able to make financial reports. This research aims to prepare financial reports for the laundry service business "IO LAUNDRY" located on Jln. Kapten Rahmad Buddin, Medan Marelan in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities. The results of this research show the financial reports of the IO LAUNDRY service business in the form of profit and loss reports, capital changes reports, balance sheets. This research is expected to provide information for IO LAUNDRY business owners in implementing Financial Accounting Standards for Micro, Small and Medium Entities. Based on the results of the discussion that has been described in the previous chapters in this research and based on the data and information that has been obtained in this research, it can be concluded as follows that from the results of research for three months, namely January, February and March, then IO LAUNDRY can find out how much income/profit was earned during those three months, namely IDR 48,850,000.-. Regarding IO LAUNDRY's readiness to implement SAK-EMKM as the basis for financial reports, in this case in terms of perception indicators and supporting facilities, it can be said that Medan city MSME players are quite ready to make financial reports based on SAK-EMKM.